Effective Larval Foraging in Large, Low-Diet Environments by Anopheles gambiae - A. C. Sutcliffe; M. Q. Benedict (Psyche: A Journal of Entomology)
Adult mosquito size is constrained by conditions experienced in the larval stage including the amount and quality of diet. The energy expended collecting diet depends partly on its concentration, the water depth, and the mosquito species. In order to better understand these interactions, individual Anopheles gambiae s.s. Giles were cultured to the adult stage in three types of experiments in which one of the following conditions was fixed and the other two were varied: water volume, diet amount, and diet concentration. In addition to survival, days of development to pupation and wing length were determined. The same outcomes were measured in experiments for which special containers were constructed that allowed the detection of chemical and tactile interactions. Larvae were able to develop to adulthood in volumes as great as 30 mL/larva when diet was added at an average rate of only 7 μg/mL/day. The results demonstrate effective foraging in large low-diet volumes far above what had previously been estimated.